Clinical Neurophysiology Fellowship Program Directors Survey on a Standardized Fellowship Match Process: A Call for Action. Issue 7 (14th November 2022) - Karakis, Ioannis; Liu, Lynn; Bensalem-Owen, Meriem; LaRoche, Suzette M.; Lopez, Jaime R.; Schmitt, Sarah E.; Britton, Jeffrey W.; Nuwer, Marc R.; Lee, Leslie H.; Rubin, Devon I.; Laughlin, Ruple S.; Sinha, Saurabh R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: To survey US Clinical Neurophysiology (CNP) fellowship program directors on the nature of CNP and related training programs, current recruitment cycle, and views for a standardized process. Methods: A 23-question electronic survey was sent to all 93 US Accreditation Council for Graduate Medical Education-accredited CNP fellowship program directors from December 2020 to January 2021. Results: The response rate was 60%. There was great variability in the number of CNP positions and CNP tracks offered. The following tracks were identified: 48% EEG dominant, 26% EMG dominant, 22% split equally between EEG and EMG, and 2% and 1% were neurophysiologic intraoperative monitoring and autonomic dominant, respectively. Of the responding institutions, 43% offered a second year of training options to CNP fellows, mainly in conjunction with Epilepsy fellowship, which was pursued by 25% of CNP fellows. Many programs indicated flexibility in their design between different CNP tracks or between CNP and other related training programs based on the available candidates. The median percentage of CNP fellowship positions filled over the last 5 years was 80%, and there was great variation in the recruitment timeline across institutions. Overall, 86% of program directors favored a universal timeline and 71% favored a formal match for CNP. The respondents were split between an independent CNP match (39%) and joining the initiatives of affiliate societies on a standardized process (61%). Conclusions: There is significant heterogeneity in the makeup of the CNP fellowship programs and the recruitment process. The majority of CNP program directors are in favor of standardization of the recruitment process.